2014
DOI: 10.1016/j.semcdb.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

RhoGTPases, actomyosin signaling and regulation of the Epithelial Apical Junctional Complex

Abstract: Epithelial cells form regulated and selective barriers between distinct tissue compartments. The Apical Junctional Complex (AJC) consisting of the tight junction (TJ) and adherens junction (AJ) control epithelial homeostasis, paracellular permeability and barrier properties. The AJC is composed of mutliprotein complexes consisting of transmembrane proteins that affiliate with an underlying perijunctional F-actin myosin ring through cytoplasmic scaffold proteins. AJC protein associations with the apical actin-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 118 publications
(122 reference statements)
2
86
1
Order By: Relevance
“…(Quiros and Nusrat, 2014; Ratheesh and Yap, 2012) (Figure 1). E-cadherin forms both small spot-like clusters along the lateral membrane as well as an apical belt-like structure, the “zonula adherens” (ZA), which is located just basal to the TJ.…”
Section: Linkage Of Core Tj and Aj Proteins To The Actomyosin Cytoskementioning
confidence: 99%
See 1 more Smart Citation
“…(Quiros and Nusrat, 2014; Ratheesh and Yap, 2012) (Figure 1). E-cadherin forms both small spot-like clusters along the lateral membrane as well as an apical belt-like structure, the “zonula adherens” (ZA), which is located just basal to the TJ.…”
Section: Linkage Of Core Tj and Aj Proteins To The Actomyosin Cytoskementioning
confidence: 99%
“…A role for Rho GTPases in regulating cell-cell junctions was first established by studies showing that manipulating GTPase function with constitutively active or dominant negative Rho GTPases or with inhibitors disrupted junctional integrity (Citi et al, 2014; Quiros and Nusrat, 2014; Ratheesh et al, 2013). These studies demonstrated that Rho GTPases are important regulators of both the AJ (Braga et al, 2000; Braga et al, 1999; Braga et al, 1997; Takaishi et al, 1997) as well as the TJ (Jou et al, 1998; Nusrat et al, 1995).…”
Section: Rho Family Gtpases Are Critical Regulators Of Cell-cell Juncmentioning
confidence: 99%
“…Among them, signaling pathways of Rho family have been reported to exert a variety of effect on cellular structure and function9. Studies have shown that RhoA/Rho-associated coiled-coil containing protein kinase-1 (ROCK-1), a major downstream effector of RhoA, is involved in I/R injury and, particularly, has a regulatory effect on energy metabolism.…”
mentioning
confidence: 99%
“…It is localized to the apical half of the lateral membrane of the epithelial cell and is composed of tight junctions (TJs) and adherens junctions (AJs). While AJs (and, to some extent, desmosomes) are considered to maintain a mechanical linkage between adjacent cells, TJs are instead responsible for sealing the intercellular space to a variety of particles, thereby regulating selective paracellular solute transport [19] ( fig. 2 a).…”
Section: Paracellular Epithelial Barriermentioning
confidence: 99%